Vortex induced vibration via wind energy - Er, Yu Wei (2017)
Wind energy is a natural source of energy that is free, green and renewable. However, in current time, wind energy is underutilise commercially in the global scale. This may be due to its inability to generate electricity efficiently as wind is not readily available all the time. The purpose of this project is to study the effects of vortex inducted vibration via wind energy. The experiment will be carried out using a wind tunnel with wind speed ranging from 1m/s to 10m/s with cantilever length ranging from 0.15m to 0.4m. The second phase of this project will focus on harvesting electrical energy using a piezoelectric transducer, attached to the cantilever beam.